Cloning and characterization of a region of the Enterococcus faecalis conjugative plasmid, pCF10, encoding a sex pheromone-binding function. - Ruhfel, R E (1993)
In order to investigate the mechanism by which peptide sex pheromones induce expression of the conjugation functions of certain Enterococcus faecalis plasmids, a biological assay was developed to measure the ability of cells carrying the conjugative plasmid pCF10 to bind the sex pheromone cCF10. The data indicated that pCF10 endows its host E. faecalis cell with the ability to specifically remove (apparently by irreversible binding) cCF10 activity from culture medium. The pCF10 DNA encoding this ability was localized to a 3.4-kb segment within a region involved in negative control of expression of conjugal transfer functions. This segment also encoded ability to bind the pheromone inhibitor peptide iCF10. DNA sequencing revealed three open reading frames, which have been denoted prgW (pheromone responsive gene W), prgZ, and prgY. The deduced product of prgW resembled regulatory proteins from other bacteria and eucaryotes, with a very high degree of identity within a putative DNA-binding domain. The prgY gene actually extended into an adjacent region of pCF10 and could encode a protein with significant similarity to a protein called TraB, believed to be involved in shutdown of pheromone cAD1 production by cells carrying the pheromone-inducible hemolysin plasmid pAD1, according to F.Y. An and D.B. Clewell (Abstr. Gen. Meet. Am. Soc. Microbiol. 1992, H70, 1992). The prgZ gene product showed significant relatedness to binding proteins encoded by oligopeptide permease (opp) operons in gram-positive and gram-negative bacteria and is highly similar to a pAD1-encoded protein, TraC, which is believed to mediate sex pheromone cAD1 binding (K. Tanimoto, F. Y. An, and D. B. Clewell, submitted for publication). A Tn5 insertion into prgZ abolished cCF10 binding ability.